Visual inspection of hazardous trees assessment methods in amenity forests of Peninsular Malaysia - Othman, Helmy Tariq (2017)
Visual inspection to identify potential hazardous tree is a useful tool during tree inspections. Since amenity forests in Peninsular Malaysia have become popular and attract tourists for recreation activities, inspection for hazardous tree at amenity forest becoming crucial. Forest Department Peninsular Malaysia has produced guideline for inspection of hazardous tree that is based on International Society of Arboriculture (ISA) with modifications to adapt Malaysian forest conditions as well as department’s requirement of tree asessments. The aims of this study are to (i) review and compare the results of tree hazardous assessment between two methods, FDPM method and ISA method and (ii) examine the number, structure and species as well as level of hazardous trees at selected amenity forests. Based on the results, 819 trees from the study areas were potentially hazardous. The trees were from 48 families, 99 genera and 144 species. At the tree family level, 29.67% of the trees were from Dipterocarpaceae. In term of individual species, Syzygium syzygioides is the most potential hazardous species in the study areas with 44 individuals followed by Dryobalanops oblongifolia and Koompassia malaccensis. Negeri Sembilan among other states and Ulu Bendol Amenity Forest among other amenity forests has shown to have the highest number of tress with potentially hazardous. Results also shown that from FDPM method, the level of hazardous trees in the study areas was rated as 7 to 9 whereas ISA method was rated as 6 to 8. FDPM and ISA method have showed to have similarity of patern in resulting the potentially hazardous tree and concluded that FDPM method can be potentially applied on hazardous tree assessment in other amenity forests in Peninsular Malaysia.